How to Run POSIX Apps in a Minimal Picoprocess - Howell, Jon; Parno, Bryan; Douceur, John (JD) (Proceedings of the USENIX Annual Technical Conference, 2013)
We envision a future where Web, mobile, and desktop applications are delivered as isolated, complete software stacks to a minimal, secure client host. This shift imbues app vendors with full autonomy to maintain their apps' integrity. Achieving this goal requires shifting complexity out of the client platform and replacing the required behavior inside the vendors' isolated apps. We ported rich, interactive POSIX apps, such as Gimp and Inkscape, to a spartan host platform. We describe this effort in sufficient detail to support reproducibility.